Short-term carbon mineralization from soils under different land uses in northwest India - Manju Sharma; Raj Setia; Madhuri Rishi; Vinod Kumar; Randhir Singh; Brijendra Pateriya (Soil Advances)
Soil respiration is an indicator of soil microbial activities. Soil respiration rates vary significantly with soil type and structure, but these relationships are not fully understood. This study investigated the controls of soil respiration under different land uses to improve models and predict soil carbon dynamics across different landscapes. A total of 32 surface soils (0–15 cm) were collected from cropland, forest, plantation and scrubland (eight samples from each land use) in the Shaheed Bhagat Singh Nagar district of Punjab (India). In a laboratory incubation experiment, these soils were left unamended or amended with wheat residues (2 % w/w) and CO2 release was measured over 28 days at constant temperature and soil water content. Cumulative CO2 emission per g soil (Cmin, CO2 mg per g soil) in control and wheat residue amended soils after 28 days were in the order: Forest (0.097 for control soils and 0.580 for residue amended soils)∼ Scrubland (0.089 for control soils and 0.535 for residue amended soils)> Plantation (0.065 for control soils and 0.400 for residue amended soils) > Cropland (0.058 for control soils and 0.360 for residue amended soils). Higher mineralizable C (Cmin) and Cumulative CO2 emission per g soil organic carbon (qM) in forest soils was related to total organic carbon and POXC (permanganate oxidizable C). The one compartment model fitted the cumulative CO2 data very well than the two-compartment model which implies that the rate of decomposition of organic matter depends on availability of the substrate. The potential mineralizable C (Co) was higher (8.96 times higher across all the four land uses), but rate constant (k) was significantly (p < 0.05) lower (1.36 times higher across all the four land uses) in wheat residue amended soils than control soils. The study showed that soil respiration mainly depends on available phosphorus, clay content, and bulk density of soils among different land uses. They could also be used as sensitive indicators for the sustainable management of soils and their contribution to regional climate change.